High-Flow Nasal Oxygen in Coronavirus Disease 2019 Patients With Acute Hypoxemic Respiratory Failure: A Multicenter, Retrospective Cohort Study*. Issue 11 (November 2020) - Xia, Jingen; Zhang, Yi; Ni, Lan; Chen, Lei; Zhou, Changzhi; Gao, Chang; Wu, Xiaojing; Duan, Jun; Xie, Jungang; Guo, Qiang; Zhao, Jianping; Hu, Yi; et al.
Abstract : Objectives: An ongoing outbreak of coronavirus disease 2019 is spreading globally. Acute hypoxemic respiratory failure is the most common complication of coronavirus disease 2019. However, the clinical effectiveness of early high-flow nasal oxygen treatment in patients with coronavirus disease 2019 with acute hypoxemic respiratory failure has not been explored. This study aimed to analyze the effectiveness of high-flow nasal oxygen treatment and to identify the variables predicting high-flow nasal oxygen treatment failure in coronavirus disease 2019 patients with acute hypoxemic respiratory failure. Design: A multicenter, retrospective cohort study. Setting: Three tertiary hospitals in Wuhan, China. Patients: Forty-three confirmed coronavirus disease 2019 adult patients with acute hypoxemic respiratory failure treated with high-flow nasal oxygen. Interventions: None. Measurements and Main Results: Mean age of the enrolled patients was 63.0 ± 9.7 years; female patients accounted for 41.9%. High-flow nasal oxygen failure (defined as upgrading respiratory support to positive pressure ventilation or death) was observed in 20 patients (46.5%), of which 13 (30.2%) required endotracheal intubation. Patients with high-flow nasal oxygen success had a higher median oxygen saturation (96.0% vs 93.0%; p < 0.001) at admission than those with high-flow nasal oxygen failure. High-flow nasal oxygen failure was more likely in patients who were older ( p = 0.030) and male ( p = 0.037), had a significant increase in respiratory rate and a significant decrease in the ratio of oxygen saturation/FIO2 to respiratory rate index within 3 days of high-flow nasal oxygen treatment. In a multivariate logistic regression analysis model, male and lower oxygen saturation at admission remained independent predictors of high-flow nasal oxygen failure. The hospital mortality rate of the cohort was 32.5%; however, the hospital mortality rate in patients with high-flow nasal oxygen failure was 65%. Conclusions: High-flow nasal oxygen may be effective for treating coronavirus disease 2019 patients with mild to moderate acute hypoxemic respiratory failure. However, high-flow nasal oxygen failure was associated with a poor prognosis. Male and lower oxygenation at admission were the two strong predictors of high-flow nasal oxygen failure. Abstract : Supplemental Digital Content is available in the text.